Inter‐ and Intra‐rater Agreement of Dermatologic Ultrasound for the Diagnosis of Lobular and Septal Panniculitis. (27th June 2019) - Romaní, Jorge; Giavedoni, Priscila; Roé, Esther; Vidal, David; Luelmo, Jesús; Wortsman, Ximena
Abstract : Objectives: Dermatologic ultrasound (US) may aid in the diagnosis and classification of panniculitis. The purpose of this study was to assess the capability of dermatologic US for subtyping mainly septal/lobular panniculitis. Methods: A multicentric and prospective study of the inter‐ and intra‐rater agreement of dermatologic US for subtyping panniculitis was conducted among 4 clinicians with experience in dermatologic US and a radiologist specialized in dermatologic US. Clinicians recruited patients and performed dermatologic US examinations of the most substantial lesion and punch biopsies. A histologic study was considered the reference standard. Then the images were blindly evaluated by all researchers. For intra‐ and inter‐rater agreement, Cohen and Fleiss κ values were calculated. Results: Sixty‐four patients were included. The Cohen intra‐rater κ was 0.74. Sensitivity and specificity for lobular panniculitis were 85.19 and 88.57, respectively. The Fleiss inter‐rater κ was 0.47. Limitations of the study included the small number of patients and differences in evaluators and their dermatologic US equipment. Conclusions: This study supports the use of US for diagnosing panniculitis. For subtyping panniculitis, the intra‐rater correlation was good. Improvement of inter‐rater agreement may depend on access to clinical information, dynamic images, a better definition of criteria, homogeneous configurations of the devices, and the expertise of dermatologic US operators.